2021
DOI: 10.1021/acsnano.1c06564
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Study of Exciton Transfer in Sb(III)-Doped Two-Dimensional [NH3(CH2)4NH3]CdBr4 Perovskite

Abstract: Antimony-based metal halide hybrids have attracted enormous attention due to the stereoactive 5s2 electron pair that drives intense triplet broadband emission. However, energy/charge transfer has been rarely achieved for Sb3+-doped materials. Herein, Sb3+ ions are homogeneously doped into 2D [NH3(CH2)4NH3]­CdBr4 perovskite (Cd-PVK) using a wet-chemical method. Compared to the weak singlet exciton emission of Cd-PVK at 380 nm, 0.01% Sb3+-doped Cd-PVK exhibits intense triplet emission located at 640 nm with a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
85
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(93 citation statements)
references
References 53 publications
7
85
0
Order By: Relevance
“…The photoluminescence excitation (PLE) spectrum consists of two different bands around 290 and 340 nm (Figure a). Typically, Sb 3+ possesses an allowed 1 S 0 – 1 P 1 and a partially allowed 1 S 0 – 3 P 1 transition named C and A bands, respectively, which reportedly split into a triplet and a doublet due to a pseudo-Jahn–Teller effect. ,, The PLE spectrum of Cs 2 CdCl 4 :Sb 3+ follows this predicted behavior, with the A band evidenced by the features at ∼350 and 333 nm and the C band evidenced by the signals at 293 and ∼280 nm (Figure S9), mostly resembling the bulk material . The third peak of the triplet, which is expected to be around 270 nm, might be partially shadowed by other features.…”
Section: Resultsmentioning
confidence: 79%
“…The photoluminescence excitation (PLE) spectrum consists of two different bands around 290 and 340 nm (Figure a). Typically, Sb 3+ possesses an allowed 1 S 0 – 1 P 1 and a partially allowed 1 S 0 – 3 P 1 transition named C and A bands, respectively, which reportedly split into a triplet and a doublet due to a pseudo-Jahn–Teller effect. ,, The PLE spectrum of Cs 2 CdCl 4 :Sb 3+ follows this predicted behavior, with the A band evidenced by the features at ∼350 and 333 nm and the C band evidenced by the signals at 293 and ∼280 nm (Figure S9), mostly resembling the bulk material . The third peak of the triplet, which is expected to be around 270 nm, might be partially shadowed by other features.…”
Section: Resultsmentioning
confidence: 79%
“…15 In addition, Luo's group reported that upon doping Sb 3+ into a 2D-structured [NH 3 (CH 2 ) 4 NH 3 ]CdBr 4 perovskite, a PLQY of close to 1 was achieved. 16 Other studies have shown that Sb 3+ is an excellent luminescent center. 11,17 Therefore, further studies on the relationship between the emission intensity and the structural distortion of Sb 3+ -doped OIMHs are required.…”
Section: Introductionmentioning
confidence: 96%
“…In order to devise a rational strategy to demonstrate synthetic control over modulation of the structure and luminescence properties of 0D Mn­(II) halide hybrids, we turned our attention to d 10 transition metal halide-based hybrids as a potential host material. Recently, many have reported on 0D Cd­(II) and Zn­(II) halide hybrids that show broadband emission arising due to the significant emission contribution by the organic ligand. ,, Zn­(II) halide-based 0D hybrids typically crystallize with the [ZnX 4 ] 2– tetrahedral unit as a building block. ,,, Noteworthy, Cd­(II) halide-based 0D hybrids can show the [CdX 6 ] 4– octahedral or [CdX 4 ] 2– tetrahedral coordination environment depending upon the nature of the organic ligand and the halide type. , Such transition metal halide-based 0D hybrids are known to adopt a variety of structures that can potentially be exploited as a host material/starting framework. These host materials can further be doped with Mn­(II) ions to exert synthetic control on modulating the local structure and emissive properties of 0D Mn­(II) halide hybrids.…”
Section: Introductionmentioning
confidence: 99%